2020
DOI: 10.1515/rams-2020-0031
|View full text |Cite
|
Sign up to set email alerts
|

Nanocrystalline graphite thin layers for low-strain, high-sensitivity piezoresistive sensing

Abstract: Bulk nanocrystalline graphite has been investigated as a possible candidate for piezoresistive sensors. The thin films were grown using capacitively coupled plasma enhanced chemical vapor deposition and a technological workflow for the transfer of the active material onto flexible substrates was established in order to use the material as a piezoresitive element. Preliminary electrical measurements under mechanical strain were performed in order to test the piezoresistive response of the material and promising… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 40 publications
0
11
1
Order By: Relevance
“…As a last comment, Zhao et al [ 24 ] reported that as they reduced the grain size from 25 to 8 nm, the GF increased from 11 to 600. Also, Simionescu et al [ 33 ] reported a varying GF (50–250) for a strain range of 0%–1%. In this work, NCG with lower grain sizes has been obtained; however, the GF does not appear to further increase and remains comparable to the values of previously reported works.…”
Section: Resultsmentioning
confidence: 99%
“…As a last comment, Zhao et al [ 24 ] reported that as they reduced the grain size from 25 to 8 nm, the GF increased from 11 to 600. Also, Simionescu et al [ 33 ] reported a varying GF (50–250) for a strain range of 0%–1%. In this work, NCG with lower grain sizes has been obtained; however, the GF does not appear to further increase and remains comparable to the values of previously reported works.…”
Section: Resultsmentioning
confidence: 99%
“…The deposition technique offers the advantage of growing the films directly on an insulating layer (i.e., SiO ), thus eliminating the need for an ulterior transfer step, which, for example, is required for the SLG thin films. The bulk-NCG thin films are grown with a previously established process [ 37 , 38 , 39 ], in a CH :H (60:75 sccm) atmosphere, at a pressure of 200 Pa and an RF discharge power of 100 W. The substrate temperature is kept at a high value of 890–900 °C, over a two h plasma growth step, to promote a high nucleation density. This in turn will result in thin films with high edge defect density, which is beneficial for sensors that rely on conductivity variations due to particle surface adsorption [ 37 ].…”
Section: Materials and Methodsmentioning
confidence: 99%
“…To improve the properties of sensors, flexible sensors with diverse structures have been prepared by various processing methods; including electrospinning, vapor chemical deposition, casting, and 3D printing technology 10–12 . However, these methods are disadvantageous in terms of low efficiency, high cost, and difficult industrial production.…”
Section: Introductionmentioning
confidence: 99%
“…To improve the properties of sensors, flexible sensors with diverse structures have been prepared by various processing methods; including electrospinning, vapor chemical deposition, casting, and 3D printing technology. [10][11][12] However, these methods are disadvantageous in terms of low efficiency, high cost, and difficult industrial production. Biaxial stretching is a simple and effective film preparation technology, which is also a deformation form in some polymer processing approaches, such as thermoforming, film blowing, and extrusion.…”
mentioning
confidence: 99%